2009
DOI: 10.1063/1.3118967
|View full text |Cite
|
Sign up to set email alerts
|

The ground state rotational spectrum of the fluorosulfate radical

Abstract: The rotational spectra of the fluorosulfate (FSO(3)) molecular radical in its vibronic ground state were measured in the millimeter-wave region and analyzed in detail using the matrix elements of the rotational, fine, and hyperfine Hamiltonian terms. The analysis of the assigned transition frequencies made it possible to derive very precise values of the rotational, centrifugal distortion and fine structure constants and to confirm the C(3v) molecular symmetry of the vibronic ground state unambiguously. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The measurements were made in the frequency range between 90 and 672 GHz with the Prague semiconductor millimetre-wave high resolution spectrometer. This spectrometer was described in previous papers [6][7][8]. Frequency modulation was used with the second harmonic lock-in detection.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were made in the frequency range between 90 and 672 GHz with the Prague semiconductor millimetre-wave high resolution spectrometer. This spectrometer was described in previous papers [6][7][8]. Frequency modulation was used with the second harmonic lock-in detection.…”
Section: Methodsmentioning
confidence: 99%
“…The latter is of additional interest in that it uses an Euler approximation to mitigate the non-convergence of the distortion Hamiltonian -a problem more commonly associated with water. Other species whose production involve solids and high temperature reaction such as NaH [108], MnH [109], HBS [110], ClClO 2 [111], HOONO [112] and CrCN [113] have also been reported as has pyrolysis for the production of FSO 3 [114], and photolysis for the production of SO [115].…”
Section: Unstable Speciesmentioning
confidence: 97%
“…This detailed theoretical study of the FSO 3 radical provides the results that contrary to the recent experimental study [7], single reference ab initio methods prefer the equilibrium geometry structure in C s symmetry point group. On the other hand, the DFT with both non-Hartree-Fock functionals (B3LYP and MPW3LYP) converge to the C 3v structure even if symmetry is free and if the symmetry is free they provide not only vibrational frequencies but also centrifugal distortion constants with a very good agreement with experiment.…”
Section: Discussionmentioning
confidence: 51%
“…All these failures led Warren to propose that the ground state may be E rather than A 2 or that it may be distorted (dynamically or statically) from the C 3v to the C s point group symmetry [6]. Finally, in 2009, experimental measurements based on the EPR, IR [4], and high-resolution microwave spectra [7] confirmed the C 3v symmetry of the ground state. The authors explained previous unassigned features such as the combination bands and suggested that, e.g., the unexpectedly low level of the m 6 vibration arises from the pseudo-Jahn-Teller effect, which is common in such radicals [8].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation